2017
DOI: 10.1103/physreva.96.021403
|View full text |Cite
|
Sign up to set email alerts
|

Localizing high-lying Rydberg wave packets with two-color laser fields

Abstract: We demonstrate control over the localization of high-lying Rydberg wave packets in argon atoms with phase-locked orthogonally polarized two-color (OTC) laser fields. With a reaction microscope, we measured ionization signals of high-lying Rydberg states induced by a weak dc field and blackbody radiation as a function of the relative phase between the two-color fields. We find that the dc-field ionization yields of high-lying Rydberg argon atoms oscillate with the relative two-color phase with a period of 2π wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 51 publications
(43 reference statements)
1
28
0
1
Order By: Relevance
“…More details on the experimental setup can be found in our previous publications [10,22,23].Previously, we developed a method to characterize Rydberg states in atoms and molecules formed during strong field interaction. This method employs coincidence detection of Rydberg electrons released by tunnel ionization in the spectrometer dc field and single photon ionization by blackbody radiation (BBR) [10,11]. During the strong field interaction, one electron (e1) is removed through strong field ionization and a second electron ((e2)) is trapped in high-lying Rydberg states to form Ar + * .…”
mentioning
confidence: 99%
“…More details on the experimental setup can be found in our previous publications [10,22,23].Previously, we developed a method to characterize Rydberg states in atoms and molecules formed during strong field interaction. This method employs coincidence detection of Rydberg electrons released by tunnel ionization in the spectrometer dc field and single photon ionization by blackbody radiation (BBR) [10,11]. During the strong field interaction, one electron (e1) is removed through strong field ionization and a second electron ((e2)) is trapped in high-lying Rydberg states to form Ar + * .…”
mentioning
confidence: 99%
“…When exposed to strong laser fields, a wealth of fascinating phenomena are manifested in molecules such as the bond softening and hardening [1][2][3][4], the abovethreshold dissociation [5,6], the Coulomb explosion [7][8][9], the directional bond breaking [10][11][12][13][14][15], and the chargeresonance-enhanced ionization (CREI) [16][17][18][19]. Besides the ionization, there is a certain probability for the neutral atoms to survive in strong laser fields [20,21], where the detached slow electrons would be eventually recaptured into Rydberg orbitals [22,23]. The Rydberg excitation plays important roles in the acceleration of neutral atoms [24], the formation of low-energy structures of photoelectrons [25][26][27], and the near-threshold harmonics generation [28].…”
mentioning
confidence: 99%
“…During the flight of the excited ion (Ar +* ) to the detector, the spectrometer field (with strength of a few V/cm, which is applied to guide the charged particles to the detectors) or black-body radiation (BBR) further ionizes the highly excited ion and the Rydberg electron is detached. In recent studies, we demonstrated the coincidence detection of Rydberg electrons with ionization induced by the spectrometer field and BBR in the case of single ionization [6,7]. The experimental setup and the correlated signals of Rydberg electrons with their parent ions (Ar 2+ ), which are represented as a long parabolic curve in the photo-electron-photo-ion coincidence (PEPICO) distribution, are shown in Fig.…”
Section: Experiments and Resultsmentioning
confidence: 99%